Characteristics of Bali Bull (Bos Sondaicus) Sexed Sperms with Freeze Dry Egg White at Different Incubation Time: english - Putri Damayanti; Muhammad Yusuf; Ambo Ako; Sahiruddin (Hasanuddin Journal of Animal Science (HAJAS), 2022)
The development of reproductive technology for the separation of spermatozoa with X and Y chromosomes, which is better known as sexing, can be carried out in vitro using various methods, one of which is using freeze dry egg whites. This study aims to determine the quality of semen based on incubation time. This study used four types of treatment, namely P0 = No Incubation, P1 = Incubation 30 minutes, P2 = Incubation 45 minutes, P3 = Incubation 60 minutes with six replications. Parameters observed were the quality of spermatozoa macroscopically (volume, odor, color and consistency) and microscopically (motility, abnormality, concentration, intact plasma membrane, intact acrosome cap). Y using descriptive statistical test. The results of analysis of variance that sexing spermatozoa using freeze dry egg whites at different incubation times showed a significant effect (P<0.05) on intact plasma membrane (IPM), intact acrosomal membrane (IAM), but had no significant effect P>0.05) on concentration, motility, and abnormalities. Evaluation of fresh Bali cattle spermatozoa showed results that were in accordance with the standards for further examination of semen sexing. Incubation time of 30 minutes in the sexing process of spermatozoa caused a significant decrease in motility and concentration, meanwhile, IPM and IAM of sexed spermatozoa experienced a significant decrease in incubation time of 60 minutes, but the decrease was still within the normal range for spermatozoa. to be used in the artificial insemination process. Keywords:  Sexing, incubation, concentration, motility, abnormality, intact plasma membrane, intact acrosome caps.